Village Economic Development and Empowerment Education inOptimizing Idle Land with Floating Plants - Budijono Budijono; Zulmeliza Rasyid; Endang Purnawati Rahayu; Novita Rany; Indra Suandy; Dedi Afandi (Jurnal Medika: Medika, 2026)
Optimizing idle land is one of the main challenges in improving the welfare of rural communities.This community service activity aims to provide education and guidance to village communities inoptimizing idle land through floating crop farming techniques. Idle land that is not optimallyutilized results in economic instability and food dependence. Therefore, appropriate interventionsare needed to increase the productivity and independence of rural communities. Through a seriesof trainings, workshops, and field demonstrations, participants consisting of members of VillageOwned Enterprises, Village Community Empowerment Agency employees, and community leaderswere provided with knowledge about environmentally friendly and sustainable floating cropcultivation techniques. Methods used included presentations and interactive discussions. Thisactivity also involved Village-Owned Enterprises as facilitators to improve market access andfarmer incomes. Evaluation results showed an increase in community understanding and skills inmanaging idle land, as well as the potential for increasing family income. Thus, this program isexpected to empower the village economy and create better food independence. Keywords:Environmental_sanitation; Environmental_Based_Disease; Transmission Risk.